2021
DOI: 10.15698/mic2021.10.762
|View full text |Cite
|
Sign up to set email alerts
|

Airborne bacteria in show caves from Southern Spain

Abstract: This work presents a study on the airborne bacteria recorded in three Andalusian show caves, subjected to different managements. The main differences within the caves were the absence of lighting and phototrophic biofilms in Cueva de Ardales, the periodic maintenance and low occurrence of phototrophic biofilms in Gruta de las Maravillas, and the abundance of phototrophic biofilms in speleothems and walls in Cueva del Tesoro. These factors conditioned the diversity of bacteria in the caves and therefore there a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 44 publications
6
16
0
Order By: Relevance
“…Forty‐two bacterial strains were isolated by culture techniques from the microbial mats collected in the Cueva del Viento lava tube system (Table S1 ). The mainly isolated strains belonged to the phyla Actinomycetota (43%) and Bacillota (41%) in agreement with the findings from other worldwide caves (Dominguez‐Moñino et al, 2021 ; Groth et al, 1999 ; Urzì et al, 2010 ). The phylum Pseudomonadota (12%) was observed in the 7G‐yellow and 11K‐white biofilm samples.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Forty‐two bacterial strains were isolated by culture techniques from the microbial mats collected in the Cueva del Viento lava tube system (Table S1 ). The mainly isolated strains belonged to the phyla Actinomycetota (43%) and Bacillota (41%) in agreement with the findings from other worldwide caves (Dominguez‐Moñino et al, 2021 ; Groth et al, 1999 ; Urzì et al, 2010 ). The phylum Pseudomonadota (12%) was observed in the 7G‐yellow and 11K‐white biofilm samples.…”
Section: Resultssupporting
confidence: 89%
“…The results obtained using molecular and traditional tools show disparity in terms of the major groups found in subterranean environments. With traditional isolation techniques, the most abundant microorganisms were members of the Actinomycetota and Bacillota phyla (Dominguez‐Moñino et al, 2021 ; Groth et al, 1999 ; Urzì et al, 2010 ), while the molecular approaches revealed the existence of different and specific phyla promoted by the microenvironment (De Mandal et al, 2017 ; Gonzalez‐Pimentel et al, 2018 ; Saiz‐Jimenez, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a study on the aerobiology of three Andalusian caves (Ardales, Tesoro and Gruta de las Maravillas), 19 species of Streptomyces were identified. This diversity was directly related by Dominguez-Moñino et al [53] to the abundance of phototrophic biofilms, as is the case in the ground sample.…”
Section: Prokaryotasupporting
confidence: 60%
“…Phyllobacterium is a genus of Hyphomicrobiales frequently isolated from root nodules [50], although it is also found in subterranean environments, such as Phyllobacterium catacumbae, isolated from a Roman catacomb [51]. Species of Phyllobacterium have been collected in the air of caves, such as Lascaux [52] and Ardales [53]. Likewise, different species of Phyllobacterium were found in an Etruscan tomb [54].…”
Section: Prokaryotamentioning
confidence: 99%
See 1 more Smart Citation